Pemikiran Pendidikan Islam Mohammad Natsir: Landasan Filosofis dan Implikasinya bagi Pendidikan Indonesia - Muzahid, Hizbullah; Muzhaffar, Zidan Arif; Hartadi, Hartadi; Khoir, Mulyanto Abdul (Lembaga Yasin AlSys, 2026)
This study is grounded in the gap between the ideal of Islamic education and the reality of Indonesia’s national education system, which remains dichotomous between religious and general sciences, resulting in suboptimal integration of Islamic values into national education. The study aimed to analyze the philosophical foundations of Mohammad Natsir’s thought on Islamic education, particularly the concept of tauhid, the integration of iman (faith) and knowledge, and their implications for strengthening the orientation of national education. The method employed was a Systematic Literature Review (SLR) by analyzing relevant primary and secondary literature, including books, journal articles, and scholarly works on the philosophy of Islamic education, Natsir’s thought, and national education policy. The findings indicate that Natsir’s educational thought has strong relevance for reconstructing a national education system that is religious, humanistic, and rooted in Indonesian identity through the integration of iman, knowledge, and amal (action) as the philosophical foundation of education. The study concludes that an Islamic education paradigm based on tauhid and the integration of iman–ilmu–amal can serve as a strategic reference for strengthening a holistic orientation of national education and offers conceptual implications for the development of educational policies and practices that avoid the dichotomy between religious and general sciences.